2021
DOI: 10.3390/electronics10141733
|View full text |Cite
|
Sign up to set email alerts
|

An Extended Semantic Interoperability Model for Distributed Electronic Health Record Based on Fuzzy Ontology Semantics

Abstract: Semantic interoperability of distributed electronic health record (EHR) systems is a crucial problem for querying EHR and machine learning projects. The main contribution of this paper is to propose and implement a fuzzy ontology-based semantic interoperability framework for distributed EHR systems. First, a separate standard ontology is created for each input source. Second, a unified ontology is created that merges the previously created ontologies. However, this crisp ontology is not able to answer vague or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…In public health, deep extreme learning has been used to achieve an accuracy rate of 97.59% forecasting COVID-19's spread [86]. In precision medicine, Adel et al 2021 demonstrated that clinicians can more rapidly extract needed patient data from EHRs using a fuzzy ontology-based semantic interoperability framework with an ML-based natural language processing (NLP) approach [87]. There has been extensive work in AI-augmented or intelligent imaging to improve monitoring of fetal organ development with ultrasounds (using DL with convolutional neural network (CNN)), COVID diagnoses with chest X-rays (using CNN), and even dental age in forensics (using neural networks and X-rays) [88][89][90].…”
Section: Discussionmentioning
confidence: 99%
“…In public health, deep extreme learning has been used to achieve an accuracy rate of 97.59% forecasting COVID-19's spread [86]. In precision medicine, Adel et al 2021 demonstrated that clinicians can more rapidly extract needed patient data from EHRs using a fuzzy ontology-based semantic interoperability framework with an ML-based natural language processing (NLP) approach [87]. There has been extensive work in AI-augmented or intelligent imaging to improve monitoring of fetal organ development with ultrasounds (using DL with convolutional neural network (CNN)), COVID diagnoses with chest X-rays (using CNN), and even dental age in forensics (using neural networks and X-rays) [88][89][90].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research proposes a semantic ontological framework that might unify several EHR data formats. It takes different data formats as input (ADL, SQL, XML, CDA-HL7) and converts them into an OWL ontology [49].…”
Section: Discussionmentioning
confidence: 99%
“…VEO showed better machine readability (z = 1.12), linguistic quality (z = 0.61), and domain coverage (z = 0.39) compared to a sample of cognitive ontologies. Recently, a computational study of ontological data was published [5]. The use of semantics based on fuzzy ontologies is demonstrated by first considering a separate standard ontology in each input source and then merging the developed ontologies into a unified ontology.…”
Section: Introductionmentioning
confidence: 99%